RETRACTED: Sustainable urban development in Russia within a green economy framework - Tkacheva Olga; Karashchenko Victoria; Chistyakov Anatoliy; Tsurak Ludmila; Tkachev Denis; Bogomazova Ksenia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001